A Motivation as Correlate of Job Performance Among Lecturers’ in Public Tertiary Institutions in Gombe State - Sani Yakubu Gombe; Sani Ahmed Yauta; Yusuf Mohammed Abdullahi (Generasi Sains Indonesia, 2025)
This paper has explored motivation as a job performance correlate of lecturers at the Gombe State public tertiary institutions. The research was aimed in four hypotheses which took the style of correlational research. This population comprised 2,561 lecturers out of which a sample population of 366 were selected by use of a proportionate sampling method. Two adaptations of the data collection tools were used, including the teacher motivation scale by Namutebi (2019) and a job performance questionnaire. The instruments were made to be reliable with Cronbach Alpha of 0.882 and 0.886, and the content validity was determined by use of three experts. The drop-and-pick strategy was used to administer questionnaires. The methods of data analysis included inferential statistics, and relationships were analyzed by Pearson Product Moment Correlation (PPMC), group difference was analyzed by independent sample t-tests, and one-way ANOVA was used to test the differences among groups. The results showed that there was a positive correlation of high strength between the motivation and job performance among lecturers. The difference in job performance between genders was not significantly different. The research concludes that motivation is crucial to the performance of lecturers in the Gombe State tertiary institutions of learning which are state-owned. It suggests enhancing intrinsic motivation through the development of actual interest in work and developing mentor-mentee relationships to make professional growth.